PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS IPS KELAS V SDN 31 AMPENAN - Baiq Denaya Vialya Alni; Nurhasanah; Setiani Novitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The 2013 curriculum emphasizes a student-centered learning process using active learning patterns reinforced by learning models that are appropriate to the learning material. The critical thinking abilities of class V students at SDN 31 Ampenan are still in the low category. This is because teachers mostly use conventional methods such as lectures. This research aims to determine whether there is an influence of the project-based learning model on the social studies critical thinking abilities of class V students at SDN 31 Ampenan. This type of research uses quantitative research with experimental methods using assessment instruments, observation sheets, and tests. Based on the research results, the asymptote value was obtained. Sig. (2-tailed) is 0.01 < 0.05, then H_0 is rejected and H_a is accepted, which means it can be concluded that there is a significant influence of the project-based learning model on the social studies critical thinking abilities of class V students at SDN 31 Ampenan.